The forever war - Filkins, Dexter (New York Vintage Books, 2009)
Provides a firsthand account of the battle against Islamic fundamentalism, from the rise of the Taliban in the 1990s, to the terrorist attacks of 9/11, to the wars in Afghanistan and Iraq, offering a study of the people involved from all sides of the conflict.
Originally published: New York : Alfred A. Knopf, 2008.
Includes bibliographical references (p. [347]-353) and index.
Donated by Logan Wangsgard (Hall's Book Drive) Dec. 2015.
Keywords: Iraq War, 2003-2011.; War on Terrorism, 2001-2009.; Military science